MODEL PEMBELAJARAN KOOPERATIF MELALUI PENDEKATAN NOKEN PADA MATERI KESEIMBANGAN LINGKUNGAN SEBAGAI UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI KELAS X SISWA SMA NEGERI 3 JAYAPURA - SUPRAPTO SUPRAPTO (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
This research is a development of learning model (R & D) with ADDIE approach, expected to overcome the problem of classroom learning. This research produces the following: 1) development stage in the form of: analysis, design, develompent, implementation, and evaluation of the field, 2) NOKEN approach expressed very valid by validator, 3) The effectiveness of biology learning through NOKEN approach is very good, more than 80% student activity and more than 20% grade test completion, 4) NOKEN learning approach has a response rate of over 90%, with an indication of interest to students. Based on the results obtained, NOKEN learning approach, can be used as one of the alternative pendektan new learning as an effort to improve the quality of learning in class, especially class X biology subjects Environmental balance material